Página web para la unidad educativa del milenio “10 de Noviembre” ubicada en la parroquia Los Encuentros del cantón Yantzaza de la provincia de Zamora Chinchipe - Macas Chamba, Galo Efraín (2016)
The title of this thesis is website for the PAGINA WEB PARA LA “UNIDAD EDUCATIVA DEL MILENIO “10 DE NOVIEMBRE” UBICADA EN LA PARROQUIA LOS ENCUENTROS DEL CANTÓN YANTZAZA DE LA PROVINCIA DE ZAMORA CHINCHIPE. With which it is intended to fill this need in this school and Yantzaza area. It is worth mentioning that the central problem of this investigative work, lies technological order in the province of Zamora Chinchipe and especially in the canton Yantzaza, for social, cultural and economic realities of the area, and one of them is the lack of a website to the Education Unit MILLENNIUM "10 NOVEMBER" although it is a new institution in its infrastructure, which limits communication of teachers, administrators and students, creating management gaps and academics. The central problem of the research was: How affects the implementation of a web page in the process of learning of the "EDUCATIONAL GOALS UNIT" 10 NOVEMBER "THE Yantzaza county of the province of Zamora Chinchipe? The overall objective of this research is to develop a web page for the educational unit MILLENNIUM "10 NOVEMBER" Yantzaza Canton of the Province of Zamora Chinchipe, which the above problem is attacked frontally. which is limiting the communication of teachers, administrators and students , academics and management gaps Generating To meet the objectives, structure and consistency of this thesis known methods that were used to conduct this research and field work, the methods used were: a scientist who was used to cast the problem under study, inductive than allowed measuring inductive probability and statistical arguments that was used to develop the survey results As main conclusions: 90% of teachers have title to end his career and 93% of them expressed that a web page would improve the performance of the various services that has the educational unit on November 10, as well as 59% of students; And 100% of the surveyed teachers and 98% of the students expressed interest in having an institutional web page, in addition that 65% of them would like to know information about academic aspects, which noted that there is a high need of having a web site that provides all kinds of information and with this to improve conditions in this aspect of the educational institution that is being investigated. It is recommended that you should be updated web page with information that tell students and teachers is the most important in order to promote their use and good management and carry out periodic evaluations of the use and management of the website of the educational unit of the Millennium "November 10" to correct errors and improve your presentation and information.